A comprehensive analysis of pore structures and performances of mineral admixtures modified recycled aggregate concrete based on experiment and theory. (5th December 2022) - Gao, Song; Ji, Yuan; Qin, Zhenwei; Zhang, Hengwu; Xing, Fei; Liu, Ang
Highlights: Mineral powder can reduce the porosity of cement stone, reduce the average pore diameter and the maximum aperture of RAC. SF has pozzolanic activity and some particles can react with the hydration product Ca(OH)2 of cement to form C-S-H gel. Compared with ITZOM-NM, ITZOA-OM has higher porosity content, and the pores are mainly distributed on the surface of RA. Mineral admixtures can increase the volume FD of RAC pores. Abstract: Recycled aggregate concrete (RAC) is an important form of construction waste resource utilization, but the existence of multiple interface transition zone (ITZ) leads to complex pore defects in RAC, which seriously weakens its mechanical properties and chloride ion permeability. In this paper, fly ash (FA), silica fume (SF) and mineral powder (SL) admixtures were incorporated into RAC for improving the pore structure of RAC. The effects of admixtures on the pore structure parameters and pore size distribution of RAC were detailly analyzed by means of back scattering electron imaging (BSE), mercury intrusion porosimetry (MIP) and fractal dimension theory (FDT). And the micro characteristics of porosity and pore structure in ITZ were quantitatively described. The results clearly show that the appropriate amount of admixture can reduce the porosity, average pore diameter and the maximum aperture of RAC. Furthermore, the macropores and capillary pores were significantly decreased and gradually changed into transition pores and gel pores. The refinement of pores increases the compactness of RAC, particularly the pozzolanic effect of SF. The newly generated CSH gel and the filling effect of SF greatly decrease the porosity of ITZ. In addition, the fractal dimension (FD) of pore volume exhibits a good positive linear relationship to the compressive strength and chloride ion permeability resistance of RAC.